Cross-Sectional Analysis of Carcinogenic Chemical Exposure in Healthcare Facilities: A Case Study from Benghazi - H. Elmhalli, Fawzeia; B. Elshebani, Asma (Libyan Journal of Public Health Practices, 2026)
Chemical substances used in hospital environments, including potential carcinogens, pose significant risks to both patients and healthcare workers. This study aimed to evaluate carcinogenic substances present in the formulations of selected chemicals used in hospitals and healthcare centres, including pesticides, air fresheners, detergents, and sterilisation agents. A cross-sectional study was conducted using two tools: a structured questionnaire and observational checklist to collect data from four healthcare centres in Benghazi (HGH, BMC, SAC, and SHC). A total of 94 participants were included, with the sample size calculated for an unknown population using a Z-score corresponding to an 80% confidence level. The identified products were categorised into four groups according to their function, and the presence of carcinogenic substances was analysed. Among the 54 chemical products assessed, 14 were found to contain highly hazardous compounds classified as prohibited by the World Health Organization. The results highlight the need for continuous monitoring and systematic documentation of chemical agents used in healthcare locations to reduce occupational and patient exposure to carcinogenic substances. It is recommended that Infection Control Offices maintain comprehensive records of all chemical agents in use and exercise direct oversight over their application.